Properties of a Transport Instrument for Measuring Psychological Impacts of Delay on Commuters, Mokken Scale Analysis - Rezapour, Mahdi; Veenstra, Cristopher; Cuccolo, Kelly; Ferraro, F. Richard (Frontiers in Psychology, 2021)
Abstract This study assesses the validity of instrument including various negative psychological and physical behaviors of commuters due to the public transport delay. Instruments have been mostly evaluated by parametric method of item response theory (IRT). However, the IRT has been characterized by some restrictive assumptions about the data, focusing on detailed model fit evaluation. The Mokken scale analysis (MSA), as a scaling procedure is a non-parametric method, which does not require adherence to any distribution. The results of the study show that in most regards, our instrument meets the minimum requirements highlighted by the MSA. However, the instrument data did not adhere to the minimum requirements of the “scalability” for two variables including stomach pain and increased heart rate. So, modifications have been proposed to address the violations. Although MSA technique has been used frequently in other fields, this is one of the earliest studies to implement the technique in the context of transport psychology. Keywords: Mokken scaling, item response theory; instrument; stress; transportation delay